Asyhur Al-Hurum According to Qur'anic Perspectives: Comparative Study Between Mutawalli Al-Sya`râwi and Sayyed Qutb and Relevance Current - Sayyida, Sayyida (Universitas Nurul Jadid, 2020)
This study was intended to examine how the views of al-Qur 'ân against Asyhur Al-Hurum through the interpretation of the two scholars to take two comparisons interpretation books are commentaries Mutawalli Al-Sya'râWi works Mutawalli Al-Sya'râwi, and Tafsir of Sayyid Qutb This study aims to provide penjelaskan how the interpretation of the two scholars to Asyhur Al-Hurumand explaining how its relevance today. This study included in the research literature that examines the interpretation of the two scholars about Asyhur Al-Hurum, This research is descriptive analysis, and explore in depth the two letters panafsiran including QS. Al-Baqarah verse 216 and 217. In this study the authors found that of the two books I researched commentary is commentary Mutawalli Al-Sya'râWi works Mutawalli Al-Sya'râwi, and Tafsir of Sayyid Qutb authors found the view of the Quran against Al-Hur Asyhurum Based on the interpretation of the second cleric to surah al Baqarah verse 216 and 217. They all suggested that the prohibition of war in hurumand the prohibition of murder is very relevant today. This is related to the security of the travel process prospective pilgrims and the moments when the hajj. Keywords: Asyhur Al-Hurum, According to the Perspective of the Quran, Tafsir Al-Sha'rawi Mutawâli and Tafsir of Sayyid Qutb